Using clinical practice variations as a method for commissioners and clinicians to identify and prioritise opportunities for disinvestment in health care : a cross-sectional study, systematic reviews and qualitative study /: a cross-sectional study, systematic reviews and qualitative study. (April 2015) - Hollingworth, William
No abstract available